2017
DOI: 10.1080/09168451.2017.1282812
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the texture properties of whey protein isolate/starch co-gels from fracture structures

Abstract: The effects of tapioca starch (TS) and potato starch (PS) on texture properties of whey protein isolate (WPI)/starch co-gels were investigated for fracture structures. We focused on two types of WPI network structures. In a fine-stranded structure at pH 6.8, the WPI/TS co-gel fractured similarly to the WPI single gel. The WPI/PS co-gel was broken at a lower strain and lower stress. In a random aggregation at pH 5.8, the WPI/TS co-gel reached a yielding point at a lower strain, whereas the WPI/PS co-gel fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Others indicated that the addition of TS to wheat noodles created a chewy texture because the fibrous structure inside TS extended when fractured. Moreover, the addition of PS made brittle food harder to break when compressed . Petridis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Others indicated that the addition of TS to wheat noodles created a chewy texture because the fibrous structure inside TS extended when fractured. Moreover, the addition of PS made brittle food harder to break when compressed . Petridis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Besides food and beverages, whey proteins have other numerous praiseworthy applications in food industry, as they can be easily shaped into different bases and matrices (macro-, micro-and nanostructures) suitable for carrying several types of bioactive compounds, different flavours or compounds with high nutritional value. Also, there are several reports that indicate a targeted application of whey proteins as surface-active components, texture modifiers, foaming and gelling agents, thickening agents and emulsifiers (82)(83)(84). Recent developments in this field are Single cell proteins Production of single cell protein (SCP) is one of basic steps in solving the problem of increasing demands for innovative and alternative food sources.…”
Section: Whey Protein Utilisationmentioning
confidence: 99%
“…Besides food and beverages, whey proteins have other numerous praiseworthy applications in food industry, as they can be easily shaped into different bases and matrices (macro-, micro-, and nano-structures) suitable for carrying several types of bioactive compounds, different flavours or compounds with high nutritional value. Also, there are several reports that indicate a targeted application of whey proteins as surface-active components, texture modifiers, foaming and gelling agents, thickening agents and emulsifiers (82)(83)(84). Recent developments in this field are focused on development of novel whey protein-based value-added products such as whey proteinbased edible films, hydrogels, nanoparticles, and microencapsulated products (81).…”
Section: Whey Protein Utilizationmentioning
confidence: 99%